PROFILE OF THE HUMOR STATE OF WOMEN WHO REGULARLY TAKE JUMP CLASSES AT A HEALTH CLUB IN CAMPO GRANDE, WEST OF RIO DE JANEIRO (Fiep Bulletin - online, 2011)
It is proved that human beings absorb and send an answer when they receive a stimulus. Between that stimulus and its feedback there is a structure called personality, as an individual is an informational system biologically structured. (BARRETO, 2003). Psychology analyses the internal relationship of an individual with a complete interaction of mental and body effects. This area of research is strictly related to behavior.(MIRANDA apud COELHO et. Al. , 2005, SAMULSKI, 2009). The objective of this study was to analyse the transitory state of humor of women who practice Jump classes in a health club in Campo Grande, west of Rio de Janeiro. The sample was of 15 women from 18 to 47 years, practicing physical activities for at least six months. The application of the POMS questionnaire happened before and after the Jump classes. We noticed exercising reduced the negative factors of humor and elevated vigour, through fashion. The average shows us the relevance of the improvement of the vigour scores through the reduction of scores of depression, anger, tiredness and mental confusion, increasing even more the iceberg form of the graph. It can be inferred through this research that the women who practice JUMP classes improved their psychological conditioning.
Keywords: Physical activity; POMS; Personality